(untitled) (Journal of actual problems of jurisprudence, 2023)
The article is devoted to the study of ways to regulate human rights to health in the era of artificial intelligence. In Kazakhstani judicial practice, there is no scientific development of legal issues and other issues of legal regulation of artificial intelligence. Digital health technologies are announced as an important solution to the problems and shortcomings in the provision of quality health care to achieve the Sustainable Development Goals. However, they pose a threat to privacy and privacy, which can lead to discrimination and violence, resulting in violations of health, housing, employment, freedom of assembly, expression, protection from unjustified detention, physical autonomy and security. Overall, without proper planning and safeguards, digital health technologies can increase health inequalities, widening the digital divide that separates those who can and cannot afford such interventions. This article describes the main health risks associated with digital technologies, as well as the ethical and human rights standards associated with their use. It also proposes several strategies to reduce the risks associated with digital health technologies and discusses accountability mechanisms. Key words: human rights, artificial intelligence, medical law, WHO, legal regulation.